1991
DOI: 10.1007/bf01834638
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting cosmetic outcome in breast-conserving cancer treatment — objective quantitative assessment

Abstract: A battery of objective measurements of cosmetic outcome was performed on 114 patients who had been treated by breast-preservation techniques for breast cancer. Cosmetic breast retraction, as determined by Breast Retraction Assessment (BRA) measurements, was significantly greater in patients who underwent extensive primary tumor resection, were more than 60 years old, weighed more than 150 lbs, or had a primary tumor in an upper breast quadrant. While use of a local RT boost, per se, was not a significant facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…Assessment of the cosmetic results using the ABNSW system a large excisional volume (extent of surgery), re-excision, the number of procedures, surgical techniques, postoperative complications, tumor size, location of the tumor, radiation dose, inhomogeneity, radiotherapy techniques (fraction schedules, number of radiotherapy fi elds), age, race (white patients had better cosmetic results than black patients), tamoxifen, and patient sensitivity. [25][26][27][28][29][30][31][32][33][34] Above all, the factors besides the surgical procedure, such as tumor location, tumor size, and breast size, are interesting because we have been considering how to establish new methods that are useful for every breast cancer lesion. Several authors have reported an association between a large breast size and poor cosmetic outcome after breast-conserving surgery and radiotherapy, and this effect can be explained by the greater dose inhomogeneity that arises as a result of greater tangent separation.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the cosmetic results using the ABNSW system a large excisional volume (extent of surgery), re-excision, the number of procedures, surgical techniques, postoperative complications, tumor size, location of the tumor, radiation dose, inhomogeneity, radiotherapy techniques (fraction schedules, number of radiotherapy fi elds), age, race (white patients had better cosmetic results than black patients), tamoxifen, and patient sensitivity. [25][26][27][28][29][30][31][32][33][34] Above all, the factors besides the surgical procedure, such as tumor location, tumor size, and breast size, are interesting because we have been considering how to establish new methods that are useful for every breast cancer lesion. Several authors have reported an association between a large breast size and poor cosmetic outcome after breast-conserving surgery and radiotherapy, and this effect can be explained by the greater dose inhomogeneity that arises as a result of greater tangent separation.…”
Section: Discussionmentioning
confidence: 99%
“…13,21 When patients present with nonpalpable, mammographically detectable lesions and undergo diagnostic needle localized lumpectomies, positive margins are found in 55% to 89% of the specimens. 12,20,[22][23][24][25] If a diagnosis of malignancy is made by core biopsy, followed by a needle localized therapeutic lumpectomy, several studies have shown that the incidence of positive margins can be decreased. For example, 0 of 7 patients, 22 2 of 19 patients (11%), 25 and 16 of 56 patients (29%) 23 had positive margins when a therapeutic needle localized lumpectomy was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of poor or fair cosmetic outcome in most series is 15-20% or less [7]. Surgical factors as the extent of breast tissue removed and scar orientation impact mostly on breast appearance and cosmetic outcome [8][9][10].…”
Section: Breast Appearance and Cosmetic Outcomementioning
confidence: 99%